Proximate and Anti-nutritional Properties of Two Lesser Utilized Leafy Vegetables (vitex doniana and zanthoxylum zanthoxyliodes) - E. I. , David; B. N., Akubue; H. A., Njoku (Journal of Home Economics Research, 2024)
The objective of the study was to ascertain the nutrient and anti-nutrient content of zanthoxylum zanthoxyliodes, vitex donenia leaves. Standard laboratory analytical method of AOAC procedure was used to determine the proximate composition of the samples. Analysis was carried out in triplicate, including moisture, protein, fat, ash, fibre and carbohydrate content of each sample. Data were analyzed using means and t-test at 0.05 level of significance. Results show that various nutrients were present in a considerable amount in leaves, this varied significantly between the samples at (P<0.05) and (P>0.05). The result on proximate composition shows that vitex doniana has the highest value for ash (14.25%), fibre (23%), zanthoxylum zanthoxyliodes has the highest value for moisture (37.7%), fat (3.4%), protein (6.99%) and carbohydrate (37.91%). The result on anti- nutrient value revealed that vitex doniana has the highest value in phytate (3.76m/100g) zanthoxylum zanthoxyliodes has the highest value of tannin ( 0.2335%), oxalate (0.4775%). The result showed that the vegetables contained an appreciable amount of nutrients and low level of anti- nutrient and could be included in diets to supplement our daily allowance needed by the body.